Pengaruh Model NHT (Numbered Heat Together) terhadap Motivasi dan Hasil Belajar Fiqih siswa MTsN 2 Sukoharjo - Prayoga, Sain Gerry; Nurhidayati, Indah (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
This study aims to examine: (1) the level of implementation of the cooperative learning model Numbered Heads Together (NHT) in Islamic jurisprudence (Fiqih) subjects, (2) students' learning motivation, (3) students’ learning outcomes, and (4) the effect of the NHT model on motivation and learning outcomes among Grade IX Special Program students at MTsN 2 Sukoharjo in the 2024/2025 academic year. This research used a quantitative descriptive method. The population consisted of 368 students, with a sample of 55 students (15%) selected by simple random sampling. Data collection was conducted through questionnaires and documentation, and analyzed using descriptive techniques. The results showed that: (1) the application of the NHT model was in the high category, (2) students' learning motivation was in the low category, (3) learning outcomes were in the high category, and (4) there was no significant effect of the NHT model on students' motivation and learning outcomes, with r-square values of 0.026 and 0.097 respectively. This indicates that other variables outside the study influenced learning results.   Keywords: Cooperative Learning Model Numbered Heads Together, Learning Motivation, Learning Outcomes, Fiqih Subject